Sanjad-Sakati Syndrome and Its Association with Superior Mesenteric Artery Syndrome - Osamah Abdullah AlAyed (Case Reports in Pediatrics)
Sanjad-Sakati syndrome (SSS) is an autosomal recessive disorder found exclusively in people of Arabian origin. It was first reported in the Kingdom of Saudi Arabia in 1988 and confirmed by a definitive report in 1991. The syndrome comprises of congenital hypoparathyroidism, seizures, severe growth and developmental retardation, low IQ, and atypical facial features. Supportive treatment in the form of vitamin D and growth hormone supplementation is often offered to patients suffering from SSS. This case study focuses on the steps taken to help a patient who was found to have very unusual symptoms and was later found to have superior mesenteric artery syndrome.